The Relationship Between Magnesium Level in Pregnancy with Gestational Diabetes Mellitus - Ambelina, Syntia; Djanas, Dovy; Bachtiar, Hafni (Andalas Obstetrics And Gynecology Journal, 2021)
Introduction : Magnesium is one of important micronutrients in pregnancy. Pregnant women needs higher magnesium intake than non-pregnant women at similar age. Decreased blood and cellular magnesium level was related to insulin resistance.Objective : To determine relationship between mean magnesium level in pregnant women with incidence of gestational diabetes mellitus.Methods : This was quantitative analytic study using cross sectional comparative design conducted in 8 Primary Health Care in Padang and 5 General Hospital in West Sumatra. This study was done from December 2019 until March 2020. Total sample collected was 36 samples consisted of 18 pregnant mother with gestational diabetes mellitus and 18 control sample with normal pregnancy, both were in gestational age between 24-28 weeks. Statistical analysis was done using independent sample T-test.Results : Mean magnesium level of pregnant mother with gestational diabetes mellitus was 1.85 Â± 0.12 mg/dL, while in control sample was 2.10 Â± 0.15 mg/dL. Statistical result using independent sample T-test showed significant correlation between mean magnesium level and incidence of gestational diabetes mellitus with p <0.001 (p value <0.05)Conclusion : Magnesium level during pregnancy is related to gestational diabetes mellitus incidence.Keywords: magnesium level, pregnant women, gestational diabetes mellitus